PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR SEBAGAI SALAH SATU ADDED VALUE KOMODITI SALAK SIDIMPUAN DALAM PENERAPAN ZERO WASTE DI DESA LEMBAH LUBUK RAYA KECAMATAN ANGKOLA BARAT - Syafiruddin Syafiruddin; Komala Sari Nasution; Novita Aswan; Ulidesi Siadari; Anugerah Sri Widiasyih; Yulia Windi Tanjung (COVIT (Community Service of Health), 2023)
Request for salak sidimpuan every year. is quite high but the production of salak is decreasing every year as a result of climate change and also the way of cultivation that has changed. During the harvest season, there is a surge in production which causes low prices. The main obstacle that arises is the decreasing production of salak every year. Community service activities in Lembah Lubuk Raya Village, West Angkola District, South Tapanuli Regency gave very positive results seen from the enthusiastic response of the farming community to participate in activities, both socialization activities on value added for zero waste and training in the manufacture of liquid organic fertilizer. It is hoped that this activity can continue to be carried out so that the transformation of knowledge from universities to the community can continue and provide results in economic development Keywords: Salak, Commodity, Value Added, Zero Waste, Lembah Lubuk Raya.